Diffraction of radio frequency waves by spatially modulated interfaces in the plasma edge in tokamaks. (June 2019) - Papadopoulos, A. D.; Glytsis, E. N.; Ram, A. K.; Valvis, S. I.; Papagiannis, P.; Hizanidis, K.; Zisis, A.
Abstract : The use of radio frequency (RF) waves in fusion plasmas for heating, for non-inductive current generation, for profile control and for diagnostics has been well established. The RF waves, excited by antenna structures placed near the wall of a fusion device, have to propagate through density fluctuations at the plasma edge. These fluctuations can modify the properties of the RF waves that propagate towards the core of the plasma. A full-wave electromagnetic computational code ScaRF based on the finite difference frequency domain (FDFD) method has been developed to study the effect of density turbulence on RF waves. The anisotropic plasma permittivity used in the scattering studies is that for a magnetized, cold plasma. The code is used to study the propagation of an RF plane wave through a modulated, spatially periodic density interface. Such an interface could arise in the edge region due to magnetohydrodynamic instability or drift waves. The frequency of the plane wave is taken to be in the range of the electron cyclotron frequency. The scattering analysis is applicable to ITER-like plasmas, as well as to plasmas in medium sized tokamaks such as TCV, ASDEX-U and DIII-D. The effect of different density contrasts across the interface and of different spatial modulations are discussed. While ScaRF is used to study a periodic density fluctuation, the code is general enough to include different varieties of density fluctuations in the edge region – such as blobs and filaments, and spatially random fluctuations.